Views on the Occurrence and Detection of Psycho-Emotional Disturbances in Patients with Coronary Heart Disease (Literature review) - Abdulloeva Maftuna Dilshodovna; Nasyrova Zarina Akbarovna; Ochilov Ulugbek Usmanovich (Genius Journals, 2022)
The reported prevalence of neurovegetative disorders in patients with cardiac disease varies widely. It has long been recognised that mild forms of depression are found in almost two thirds of patients in hospital following acute myocardial infarction (AMI), with major depression typically found in about 15% of patients with cardiovascular disease. This prevalence is more than two to three times that of the general population, although probably not much higher than the predicted lifetime prevalence for the general population
Keywords: Acute myocardial infarction; chronic heart failure; neurovegetative disorder; phobic disorder